MANAJEMEN PEMANFAATAN LABORATORIUM JURUSAN ILMU PENDIDIKAN DI UNIVERSITAS JAMBI - Maynanda Pratama; Mulyadi Mulyadi; Agus Lestari (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the management of laboratory utilization in the Department of Education Science at Universitas Jambi, focusing on planning, organizing, implementation, and supporting and inhibiting factors. Methods: This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving laboratory heads, lecturers, administrative staff, and students. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Results: The findings indicate that laboratory management has been implemented but not yet optimal. Planning remains simple and not systematically structured, organizing lacks clear division of roles, and implementation is still limited and not fully integrated into the learning process. Supporting factors include lecturer involvement and institutional support, while inhibiting factors involve limited facilities, absence of laboratory personnel, and underdeveloped management systems. Novelty: This study highlights the dynamics of laboratory management in the early development phase within higher education, particularly in the context of educational administration, which has received limited attention in previous studies.